Rol de las incretinas - Burgos L., Ana María (Revista Hospital Clínico Universidad de Chile, 2012)
Incretins are gut hormones that are released from gut endocrine cells following oral ingestion of nutrients. The incretin hormones include glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP). GIP and GLP-1 are jointly responsible for the so-called “incretin effect”. That is, oral administration of an amount of glucose causes a greater stimulus of insulin secretion than the same amount of glucose administered by the intravenous route. Both incretins potentiate glucose-dependent insulin secretion and enhance β-cell mass through regulation of β-cell proliferation, neogenesis and apoptosis. In contrast, GLP-1, but not GIP, inhibits gastric emptying, glucagon secretion, and food intake. The incretins share similar effects on the pancreatic β cell; however, there are a number of differences in extrapancreatic actions. Both incretins are rapidly deactivated by an enzyme called dipeptidyl peptidase 4 (DPP4). Type 2 diabetes mellitus (T2DM) is associated with abnormal incretin physiology, the incretin effect is severely reduced or absent. In patients with T2DM the secretion of GIP is near normal, but its effect on insulin secretion is severely impaired. GLP-1 secretion, on the other hand, is also impaired, but its insulinotropic action is preserved, although the potency of GLP-1 in this respect is decreased compared to healthy subjets.